Prophetic Health Maintenance: Fresh Dates and Cucumber in Balancing Hot-Cold Temperaments via Tibb al-Nabawi - Wan Ainaa Mardhiah; Mohd Shafiq Sahimi; Faisal Husen Ismail; Nurul Hidayah Tumadi; Ramdan Baba; Arwansyah Kirin (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2025)
This study presents an alternative approach to ideal body maintenance based on the Sunnah of the Prophet Muhammad (PBUH), particularly through the dietary combination of fresh dates (rutab) and cucumber within the framework of hot-cold temperament balance. In the context of Tibb al-Nabawi, foods are classified according to their thermal properties hot or cold as reflected in the Hadiths and the practices of the Prophet (PBUH). The core issue addressed in this study is the lack of a systematic scientific model that explains how this Sunnah-based dietary combination contributes to the regulation of bodily homeostasis and the attainment of an ideal physique. The main objective of this study is to formulate a holistic dietary model rooted in the Prophet’s Sunnah by integrating physiological, nutritional and spiritual dimensions. This research adopts a qualitative-descriptive methodology grounded in critical literature analysis of authentic Hadiths, classical medical texts and contemporary scientific findings in nutrition. The findings indicate that consuming seven fresh dates and seven slices of cucumber daily has the potential to support metabolic functions and regulate internal body temperature, though it does not serve as a primary source of calories. The proposed model emphasizes that dietary applications based on hot-cold principles should be adapted to individual physiological conditions whether hot, cold, thin, or overweight thus contributing to systemic bodily balance. The implications of this study extend beyond the scientific validation of prophetic dietary practices it offers a new discourse in Islamic health sciences and promotes the integration of tradition and science in shaping a spiritually rooted and culturally relevant healthy lifestyle.